The Impact of the Arab Spring on the Tunisian Economy. (5th November 2016) - Matta, Samer; Appleton, Simon; Bleaney, Michael
Abstract: We use Synthetic Control Methodology to estimate the output loss in Tunisia as a result of the "Arab Spring." Our results suggest that the loss was 5.5 percent, 5.1 percent, and 6.4 percent of GDP in 2011, 2012, and 2013 respectively. These findings are robust to a series of tests, including placebo tests, and are consistent with those from an Autoregressive Distributed Lag Model of Tunisia's economic growth. Moreover, we find that investment was the main channel through which the economy was adversely impacted by the Arab Spring.